If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 5h = 8 + 3h Solving 5 + 5h = 8 + 3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3h' to each side of the equation. 5 + 5h + -3h = 8 + 3h + -3h Combine like terms: 5h + -3h = 2h 5 + 2h = 8 + 3h + -3h Combine like terms: 3h + -3h = 0 5 + 2h = 8 + 0 5 + 2h = 8 Add '-5' to each side of the equation. 5 + -5 + 2h = 8 + -5 Combine like terms: 5 + -5 = 0 0 + 2h = 8 + -5 2h = 8 + -5 Combine like terms: 8 + -5 = 3 2h = 3 Divide each side by '2'. h = 1.5 Simplifying h = 1.5
| 7n-11=5n+7 | | 5-2thirdsx=-6 | | y=-5x^2-10x-13 | | -(9c-r)= | | 5p-11=39 | | 7*k=10+x | | -v+5+6v=1+5v+3 | | 6+2p=24 | | g+9=16 | | 6x+19=3x+13 | | y-(-9)=12 | | 18x+8x-13x= | | -(-8m+k)= | | v.19.3=96.5 | | 6b-4=-22 | | w=4+3** | | x-x^2=20 | | 3(w-9)=2(w-8) | | 21=13+q | | 71-(3x+15)=3x(x+7)+x | | 2(x+7)-(-2x-1)=3x | | 4(4m-3)-1(m-5)=-52 | | -(56x-12)= | | 6y-87=7y | | -3=14+x | | 5c-3=6c | | -64=6b-4 | | 2n-7=5n-10 | | 13-3(5x-4)=-2 | | 6x+48=8x+8 | | -4x-5x=27 | | -64=6b |